Does organizational formalization facilitate voice and helping organizational citizenship behaviors? It depends on (national) uncertainty norms - Fischer, Ronald; Ferreira, Maria Cristina; Van Meurs, Nathalie; Gok, Kubilay; Jiang, Ding-Yu; Fontaine, Johnny R J; Harb, Charles; Cieciuch, Jan; Achoui, Mustapha; Mendoza, Ma Socorro D; Hassan, Arif; Achmadi, Donna; et al. (Journal of International Business Studies, 2019)
Prosocial work behaviors in a globalized environment do not operate in a cultural vacuum. We assess to what extent voice and helping organizational citizenship behaviors (OCBs) vary across cultures, depending on employees’ perceived level of organizational formalization and national uncertainty. We predict that in contexts of uncertainty, cognitive resources are engaged in coping with this uncertainty. Organizational formalization can provide structure that frees up cognitive resources to engage in OCB. In contrast, in contexts of low uncertainty, organizational formalization is not necessary for providing structure and may increase constraints on discretionary behavior. A three-level hierarchical linear modeling analysis of data from 7,537 employees in 267 organizations across 17 countries provides broad support for our hypothesis: perceived organizational formalization is weakly related to OCB, but where uncertainty is high; formalization facilitates voice significantly, helping OCB to a lesser extent. Our findings contribute to clarifying the dynamics between perceptions of norms at organizational and national levels for understanding when employees may engage in helping and voice behaviors. The key implication is that managers can foster OCB through organizational formalization interventions in uncertain environments that are cognitively demanding.